HUMAN RESOURCE MANAGEMENT INNOVATION TO INCREASE BUMDES REVENUE IN THE DIGITAL ERA - Asmini Asmini; Ardhana Januar Mahardhani; Muhammad Nur; Bhaswarendra Guntur Hendratri; Egidius Fkun (SEAN Institute, 2023)
Changes in technology and the digital revolution have had a significant impact on many aspects of life, including the economy. As economic institutions at the village level, village-owned businesses (BUMDes) are also affected by these changes. Human resource management (HRM) innovation is crucial for BUMDes to endure and thrive in the digital era, which presents both challenges and opportunities. One of the major issues identified is the lack of digital technology-related knowledge and skills among human resources. This lack of comprehension can impede BUMDes' ability to implement and leverage digital technology to increase revenue. This study seeks to analyze the challenges BUMDes face in their HR management in order to increase revenue in the digital age. Using a qualitative methodology, this research identifies issues at BUMDEs related to HR management innovation in relation to revenue growth, and provides recommendations and strategies for maximizing HR potential. The findings of this study can provide BUMDes with insights and actionable suggestions for developing appropriate and sustainable HR management innovations. Optimizing the use of digital technology and enhancing HR competencies, BUMDes will be able to expand its market presence, enhance its competitiveness, and increase its revenue in the digital era.